2015
DOI: 10.1007/s10295-014-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in ksdD influence on the ADD/AD ratio of Mycobacterium neoaurum

Abstract: Mycobacterium neoaurum TCCC 11028 (MNR) and M. neoaurum TCCC 11028 M3 (MNR M3) significantly differ in the ratio of androst-1,4-diene-3,17-dione (ADD) to androst-4-ene-3,17-dione (AD) produced. The large fluctuations are related to the dehydrogenation activity of 3-ketosteroid-Δ(1)-dehydrogenase (KsdD). Analysis of the primary structure of KsdD showed that the Ser-138 of KsdD-MNR changed to Leu-138 of KsdD-MNR M3 because of C413T in the ksdD gene. This phenomenon directly affected KsdD activity. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Microorganisms and culture conditions. M. neoaurum M3C2 is the ksdD gene replacement strain M. neoaurum M3ΔksdD::ksdD-MNR constructed by homologous recombination (52). M. neoaurum M3C2 possesses an improved and stable phenotype that is more suitable for ADD accumulation than that of M. neoaurum M3.…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms and culture conditions. M. neoaurum M3C2 is the ksdD gene replacement strain M. neoaurum M3ΔksdD::ksdD-MNR constructed by homologous recombination (52). M. neoaurum M3C2 possesses an improved and stable phenotype that is more suitable for ADD accumulation than that of M. neoaurum M3.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of substrate recognition and selectivity are poor understood. Xie reported that S138 played an important role in maintaining the active center via hydrogen bond network of Mycobacterium neoaurum KsdD [ 43 ]. However, this residue is partial conserved in this family enzyme, which is H134 in A. simplex and S131 in R. erythropolis SQ1 (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, mutations of other sites of KstD enzymes also have been shown to influence their activity. For example, p.S138L decreased the activity of KstD1 of M. neoaurum , whereas a p.V366S increased its activity [ 46 , 47 ]. Furthermore, a p.Y125H substitution of the KstD1 from M. neoaurum ATCC 25795 had only a relatively small effect [ 10 ].…”
Section: Discussionmentioning
confidence: 99%